Life cycle cost analysis: Actual problem in industrial management - Elmakis, David; Lisnianski, Anatoly (Journal of Business Economics and Management, 2006)
The reliability associated costs are the main part of total life cycle cost for any repairable system. The paper presents the history of life cycle cost analysis, its principles and applicable standards. It analyzes the reasons behind the contradiction between the great theoretical achievements and their relatively rare applications in practice. It was shown that incorrect management is the main reason. Measures for management improvement were suggested. First published online: 14 Oct 2010